A polymer-crosslinker-nanoparticles formulation for effective sand consolidation in loose sandstone formations - Mysara Eissa Mohyaldinn; Emmanuel Bullen Lado Solomon; Moamen Hassan Mohamed; Fahd Saeed Alakbari; Mohammed A. Ayoub (Journal of Petroleum Exploration and Production Technology)
Abstract Sand production in weakly consolidated sandstone reservoirs presents a significant challenge for hydrocarbon recovery, affecting both the reservoir stability and productivity. This study introduces a novel chemical sand consolidation formulation comprising polyacrylamide, chromium(III) acetate, and nano-silica, aimed at enhancing sand control while minimizing permeability reduction. The stability, rheological properties, and compressive strength of the formulation were experimentally evaluated at reservoir-relevant temperatures (25–80 °C) using bottle tests, rheometry, and unconfined compressive-strength measurements. The optimal formulation, containing 9500 ppm polyacrylamide, 2612.5 ppm chromium(III) acetate, and 6500 ppm nano-silica, achieved a compressive strength exceeding 3552.23 kPa, surpassing the typical requirements for weak sandstones. Core flooding experiments indicated a permeability reduction, which was attributed to modifications in the post-gelation pore structure rather than extensive pore blockage. Although the formulation effectively consolidates the formation, minimizing the impact on permeability is crucial for maximizing hydrocarbon recovery. Future research should focus on refining the formulation and injection strategies to further mitigate permeability reduction and optimize the balance between sand control and permeability retention. This innovative approach, incorporating nanoparticles and a lower concentration of the less toxic chromium(III) acetate, offers a promising alternative to conventional sand consolidation methods, with the potential for improved environmental compatibility.